PEMBERDAYAAN SANGGAR TANI MUDA MELALUI PELATIHAN PEMBUATAN TRICHODERMA DI DESA SUKOWIRYO KECAMATAN JELBUK KABUPATEN JEMBER - Ayamilah, Yasaroti; Hariyono, Kacung; Kuntadi, Ebban Bagus; Utami, Ratih Apri; Halwiyah, Lailatul; Maulidina, Niswah Saffanah; Sobah, Naqiyyah Nada; Yulianti, Annisa; Resmi, Aji Dita; Ramadhan, Adam; Akbar, Muhammad Mizan Ilham; Azzarah, Azzarah; Faradisi, Nurul Jinan; Zaujiah, Rima; Adha, Iqlina Asmara; Hakim, Norma Kamilia; Pradika, Yoga Reno Ayom; Praset, Fahmi (Universitas Mataram, 2024)
Agriculture plays a crucial role in the economy and social life in Indonesia, especially in rural areas where the majority of the population relies on this sector for livelihood and food security. However, challenges such as climate change and plant diseases, particularly Fusarium wilt in chili peppers, threaten the sustainability of the agricultural sector. This study represents the implementation of the Student Organization Capacity Strengthening Program (PPK ORMAWA) by the Student Association of Agricultural Social Economics (HIMASETA) to establish a Youth Farming Center in Sukowiryo Village, Jelbuk District, Jember Regency, as an innovative solution to local issues. This community service aims to enhance agricultural productivity in Sukowiryo Village through the use of Trichoderma as a biofungicide. The primary focus of the activity is training on the use of Trichoderma as a biological agent to combat Fusarium wilt, and educating young farmers on its benefits and application techniques. The program includes outreach, training in the production of Trichoderma using corn as a medium, and knowledge evaluation through pre-tests and post-tests. Results show a significant increase in participants' knowledge about Trichoderma, from 21% in the pre-test to 90% in the post-test, with a deep understanding of its benefits and application techniques. Regular use of Trichoderma effectively reduced Fusarium wilt incidence by 50% and increased average chili pepper yields by 15%. The program is expected to promote environmentally friendly agricultural practices and support food security in rural areas.